Review of Legal Digitalization Aspects from Using Telemedicine for Health Management in Indonesia - Rahmayanti; Viona Shafa Auliya; Manahap Cerarius; Alza Hamonangan Pasaribu; Al Ansari (Formosa Journal of Multidisciplinary Research, 2024)
Telemedicine is the practice of providing health services online or remotely using communication and information technology to connect patients with health service providers. Telemedicine is a form of health digitalization transformation and regulation which aims to provide health facilities with a wide coverage in overcoming various health service problems in Indonesia. Health services by utilizing digitalization influence the legal aspects of digital health. Thus, this article aims to discuss a review of the legal aspects of digitalization law with the use of telemedicine health services in Indonesia as well as the positive and negative impact of telemedicine on health problems in Indonesia. The method used in making this article is a review of literature in Indonesian and English published from the last 10 years to 2024. The results found are that there is a link between the legal aspects of digitalization in the health sector and long-distance digital service technology or what is called telemedicine. Indonesia currently has regulations and policies regarding digital health services and in their implementation the government still needs to develop and adapt the applicable laws.